PERENCANAAN DAKWAH AN-NADZIR DI KELURAHAN ROMANG LOMPOA KECAMATAN BONTOMARANNU KABUPATEN GOWA (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2021)
This thesis discusses An-Nadzir's Da'wah Planning in Romang Lompoa Village, Bontomarannu District, Gowa Regency. The main problem is how is the planning model of An-Nadzir's da'wah in Romang Lompoa Village, Bontomarannu District, Gowa Regency and the opportunities and challenges of An-Nadzir's da'wah in Romang Lompoa Village, Bontomarannu District, Gowa Regency. The purpose of this study is to find out how An-Nadzir's Da'wah Planning is in Romang Lompoa Village, Bontomarannu District, Gowa Regency and to find out the opportunities and challenges of An-Nadzir's da'wah in Romang Lompoa Village, Bontomarannu District, Gowa Regency in modern society.This study uses a qualitative research type with a da'wah management approach. Sources of data used are primary and secondary data sources. Collecting data using interviews, observation, and documentation. The data analysis technique used is inductive logic. The validity of this data using triangulation.The results of this study indicate that the planning model of An-Nadzir's da'wah is formulated in the form of a structure chart that will be built in the An-Nadzir believer's village, namely 7 departments which become references as well as An-Nadzir's da'wah activities in everyday life. Meanwhile, the opportunities and challenges of An-Nadzir's da'wah externally no longer get challenges like the beginning of their existence, but internally what they feel is from An-Nadzir's own congregation. The existence of An-Nadzir with his da'wah movement which is carried out in a participatory manner is able to give birth to several opportunities so that his activities can run well, including openness to various parties (not closing themselves off), establishing cooperation with the local government and the community, utilizing information and communication technology as a forum. new to exist in delivering da'wah.The implication of this research is that An-Nadzir is expected to be able to manage 7 departments well by preparing mature management to coordinate all forms of da'wah and maximize the opportunities that exist for the development of better da'wah in the future.